Indigenous Healthcare Practices among the People of Himalayan Region of Jammu and Kashmir - Singh, Ravail (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
In ancient Indian philosophical books like Ramayana, Vedas and Puranas have explained about the richness of the medicinal plants of Himalayan region. The indigenous people of Himalayan region acquire knowledge of various medicinal properties of several herbal plants and their uses to cure various diseases with the help of herbal healers and elders. These herbal plants form the basis of indigenous or traditional systems of healthcare used by the majority of remotely located people. At the same time, over-harvesting, degradation of medical plants, and losses of traditional medical knowledge in local communities are common problems in these resource areas. To keep in mind about the medical utilization and preservation of this traditional treasure of knowledge, the investigator has selected this topic with the aim to utilize the herbal plants in healthcare practices and to preserve it for the future generations with the help of education because education is the only way to aware, utilise and preserve such healthcare practices among the indigenous people. For the collection of data, interview schedule has been used by the investigator. In the present paper, it is observed by the investigator that indigenous people of Himalayan region uses more than 40 valuable herbal plant species that were identified with their relevant information and documented with regard to their botanical names, family, local names, utilization and parts used by the local regional people for different human ailments. The common diseases treated by the herbal practitioner were asthma, digestive problems, skin burning, cough, cold, snake bite, chicken pox, fever and diabetes.